Comorbidity burden on receipt of adjuvant immunotherapy and survival in patients with stage III melanoma: an analysis of the National Cancer Database. (27th June 2020) - Freeman, S. Caleb; Satish, Mohan; Walters, Ryan W.
Abstract: Background: Comorbidity burden is associated with development of cancer, stage at diagnosis, and treatment outcomes. We evaluated the association between comorbidity burden, receipt of adjuvant immunotherapy, and survival in patients with stage III melanoma. Methods: Using the National Cancer Database, we identified 16, 906 patients with stage III melanoma who underwent surgery of the primary site. Outcomes included receipt of adjuvant immunotherapy and overall survival; independent variables included Charlson/Deyo comorbidity index (CDI) and receipt of adjuvant immunotherapy. Results: Patients with CDI scores of two or more averaged 30.0% and 30.9% lower adjusted odds of receiving adjuvant immunotherapy relative to patients with a CDI score of zero or one, respectively ( P = 0.001 and 0.002, respectively). Longer survival was associated with lower CDI scores (all P < 0.001) and receipt of adjuvant immunotherapy ( P < 0.001). Patients who received adjuvant immunotherapy averaged 16.0% lower adjusted risk of death compared to patients who did not ( P < 0.001), which was constant within all CDI cohorts. Patients with a CDI score of two or more averaged 53.4% and 39.1% higher adjusted risk of death relative to patients with a CDI score of zero or one (both P < 0.001). Conclusion: Greater comorbidity burden was associated with lower receipt of adjuvant immunotherapy; however, adjuvant immunotherapy provided similar survival benefit for patients' irrespective comorbidity burden. Our findings suggest that patients with stage III melanoma who have a greater comorbidity burden may benefit from adjuvant immunotherapy but should not replace careful patient selection by the clinician.